Synthesis, characterization and Theoretical study of some 2-Oxopyridine Carbonitrile derivatives that contain tetrazole ring and evaluation of their Biological activity - Mekky, Athraa Hamed; Jaber Dalal, Meinaa; G. Sager, Athraa; Salmn , Noor Abd Alkhudhur; Abbas Talib Abd Ali; Jayapal, M.R. (University of Thi-Qar Journal of Science, 2023)
A series of 2-oxo-6-[4-(1H-tetrazol-1-yl) phenyl-1,2-dihydropyridine-3-carbonitrile 3,4-dimethoxyphenyl)-2-oxo-6-4-(1H-tetrazol-1-yl) phenyl]-1,2-dihydropyridine-3-carbonitrile and 2-oxo-6-[4-(1H-tetrazol-1-yl) phenyl]-4-(thiophen-2-yl)- 1,2-dihydropyridine-3-carbonitrile), were prepared from the reaction of 4-aminoacetophenone, sodium azide in the presence of glacial acetic acid via cyclization reaction to produce (1-(4-(1H- 1,2,3,4tetrazole-1-yl) phenyl) ethan-1-one). Followed by condensation of (1-(4-(1H- 1,2,3,4tetrazole-1-yl) phenyl) ethan-1-one) with ethyl cyanoacetate, aromatic aldehydes, and ammonium acetate at 110℃ to give(3,4-dimethoxyphenyl)-2-oxo-6-4-(1H-tetrazol-1-yl)phenyl]-1,2-dihydropyridine-3-carbonitrile and 2-oxo-6-[4-(1H-tetrazol-1-yl) phenyl-1,2-dihydropyridine-3-carbonitrile 3,4-dimethoxyphenyl)-2-oxo-6-4-(1H-tetrazol-1-yl) phenyl]-1,2-dihydropyridine-3-carbonitrile and 2-oxo-6-[4-(1H-tetrazol-1-yl) phenyl]-4-(thiophen-2-yl)- 1,2-dihydropyridine-3-carbonitrile. The synthesized compounds were characterized by spectral methods (FT-IR and 1H-NMR & 13C-NMR). The synthesized compounds have been estimated in lab. for biological efficiency. Preliminary biological testing reveals that the compounds have exhibited activity against the two types of bacteria (staphylococcus aureus, and Klebsiella pneumonia). Both Compounds had high activities. Docking experiments for the compounds were undertaken in order to better understand the ligand-protein interactions in terms were done using py-px and BIOVIA/ Discovery studio of binding affinity.